2023
DOI: 10.3390/ijms242015147
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Molecular Mechanisms Underlying Early Response to Inflammation and Helicobacter pylori Infection in Human Gastric Epithelial Cells

Giulia Martinelli,
Marco Fumagalli,
Stefano Piazza
et al.

Abstract: Helicobacter pylori is a leading cause of chronic gastric inflammation, generally associated with gastritis and adenocarcinoma. Activation of the NF-κB pathway mainly contributes to the inflammatory phenotype observed in H. pylori infection in humans and experimental models. Since the gastric epithelium undergoes rapid turnover, inflammation and pathogenicity of H. pylori result from early phase and chronically activated pathways. In the present study we investigated the early host response to H. pylori in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The gastric epithelial cells are the first line of defense against H. pylori infection [ 19 ]. They activate immunocompetent cells through TLRs, which act as sensors for the bacterium.…”
Section: Interactions Of H Pylori With Cells Of Th...mentioning
confidence: 99%
“…The gastric epithelial cells are the first line of defense against H. pylori infection [ 19 ]. They activate immunocompetent cells through TLRs, which act as sensors for the bacterium.…”
Section: Interactions Of H Pylori With Cells Of Th...mentioning
confidence: 99%
“…Accordingly, the derivatives of hydrolysis punicalin and ellagic acid were measured as well. The second phase of our study was aimed at investigating the bioactivity of CI in gastritis through a model of human non-tumoral gastric epithelial cells (GES-1) infected with H. pylori cag+ strain 26695 (ATCC ® ) [18]. The previous analytical data suggested that the stability of the polyphenolic fraction was partially affected by the gastric environment.…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…Our group previously characterized the early inflammatory response of non-tumoral gastric cells (GES-1) to cag+ H. pylori infection [ 18 ]. By the same model, we suggested that extracts from Castanea sativa Mill.…”
Section: Introductionmentioning
confidence: 99%